The efficiency of football players in one against one game in the aspect of situational factors of a sports fight - Szwarc, A.; Kromke, K.; Lipinska, P. (Archives of Budo, 2012)
Background and study aim: The aim of research was to assess the efficiency of `players-champions` performance in game situations one against one in the aspect of changing the result of a competition, the time and place of performance. Material and methods: We analyzed the game of Spanish competitors in 13 matches played in final tournaments of the World and European Championships in the years 2008-2010. The method of observation was applied. Information about the game was registered on a monitoring sheet of designed by the present authors, using criteria of performance assessment proposed by Szwarc. Activity, effectiveness and reliability of individual offensive and defensive performances were assessed in the context of realization of the aim of the game. Results: It was noted that in one match Spanish footballers, the World and European Champions, performed on average from 184 to 253 encounters in fight situations one against one with average reliability of 56%. More frequently they got engaged in offensive play and performed it more reliably than defensive actions, and the efficiency of such performance was decreasing in course of the game. When the result of the game was favorable, they used a strategy of "defensive" offensive - at first they aimed at keeping the ball and/or at winning the field with it thus transferring the gravity of the game to the opponent`s half. In circumstances of an unfavorable result, when the opponent was in possession of the ball, they tried to take it over already in the middle zone of the pitch and immediately create situations of scoring the goal. Conclusions: The World and European Champions showed efficiency in individual performances similar to the previous winners of European and World tournaments. They got engaged in offensive performances more often than in individual defensive performances, which should be recognized as a feature characteristic of their style of play.